EVALUATION FOR GENETIC VARIABILITY, CORRELATION AND PATH COEFFICIENT IN MUTANT POPULATION OF FORAGE SORGHUM (SORGHUM BICOLOR L. MOENCH) - SINGH, JOGENDRA; B. R. RANWAH; CHAUDHARY, LATA; CHHAGAN LAL; M. C. DAGLA; VINOD KUMAR (The Bioscan, 2013)
An investigation was carried out with multicut forage sorghum variety SSG 59-3 and its 15 mutants derived from gamma irradiation to study the variability parameters, correlations and path coefficient analysis for green fodder yield per plant per day and their component traits. Out of 41 significant characters, magnitude of GCV ranged from 0.71 to 42.42 per cent, PCV ranged from 0.73 to 47.70 per cent, heritability (in broad sense) ranged from 31.45 to 96.23 per cent and genetic gain ranged from 1.44 to 77.71 percent at different cuts. High genetic gain were observed for early vigour (63.68) at first cut; early vigour (62.37) followed by regeneration (51.68) and number of tillers per plant (40.36) at second cut and regeneration (77.71) followed by early vigour (44.66) and green fodder yield per plant per day (49.30) at third cut, indicating the prevalence of additive gene action for inheritance of these traits. Dry matter accumulation and dry stem weight per plant at 30 DAS (0.81), number of leaves per plant (0.58) and N content in root (0.51) at first cut; dry matter accumulation per plant at 30 DAFC (0.97) and dry leaf weight per plant at 30 DAFC (0.76) and leaf length (0.53) at second cut and; early vigour (0.97), number of tillers per plant (0.92), plant height (0.90), regeneration (0.85), leaf length (0.82), root volume (0.72), stem girth (0.68) and dry root weight (0.50) at third cut, were positively and significantly correlated at genotypic level only with green fodder yield per plant per day or its sister characters. These correlated characters also had correlation between them at different cuts. Root volume (1.42), stem girth (0.91) and leaf length (0.74) have positive and high direct effect on green fodder yield per plant per day at third cut, indicating importance of these characters and can be strategically used to improve the green fodder yield of sorghum.